GALNTL6 rs558129: A novel polymorphism for swimming performance? - Zmijewski, P.; Trybek, G.; Czarny, W.; Leonska-Duniec, A. (Journal of Human Kinetics, 2021)
The enzyme polypeptide N-acetylgalactosaminyltransferase like 6, encoded by the GALANTL6 gene, plays a role in the gut microbiome regarding regulation of short-chain fatty acids and their anti-inflammatory and resynthesis functions. It was hypothesized that the T allele of the GALNTL6 rs558129 polymorphism could have a positive effect on anaerobic metabolism. Thus, this study was performed to investigate the association between GALNTL6 rs558129polymorphism and athletic performance in swimmers. A total of 147 Polish short distance (SDS) and 49 long distance swimmers (LDS) of national or international competitive levels and 379 controls were genotyped using the real-time polymerase chain reaction (real-time PCR). We found that the carriers of the T allele (CT+TT) had a 1.56 times higher chance of being SDS (odds ratio (OR): 95%CI 1.06-2.29) than the CC homozygotes. The T allele was overrepresented in the SDS compared with controls (33.7% vs. 25.7%, p = 0.025, OR 1.40, 95% CI 1.04-1.87), but no statistically significant differences were found for LDS. This study provides evidence for an association between the GALNTL6 rs558129 polymorphism and short distance swimming athlete status. Although more replication studies are needed, the preliminary data suggest an opportunity to use the analysis of GALNTL6 polymorphism along with other variants of candidate genes and standard phenotypic assessment in power-oriented sports selection.